Viral Lysis of Photosynthesizing Microbes As a Mechanism for Calcium Carbonate Nucleation in Seawater - Lisle, John T.; Robbins, Lisa L. (Frontiers in Microbiology, 2016)
Removal of carbon through the precipitation and burial of calcium carbonate in marine sediments constitutes over 70% of the total carbon on Earth and is partitioned between coastal and pelagic zones. The precipitation of authigenic calcium carbonate in seawater, however, has been hotly debated because despite being in a supersaturated state, there is an absence of persistent precipitation. One of the explanations for this paradox is the geochemical conditions in seawater cannot overcome the activation energy barrier for the first step in any precipitation reaction; nucleation. Here we show that virally induced rupturing of photosynthetic cyanobacterial cells releases cytoplasmic-associated bicarbonate at concentrations 23-fold greater than in the surrounding seawater, thereby shifting the carbonate chemistry towards the homogenous nucleation of one or more of the calcium carbonate polymorphs. Using geochemical reaction energetics, we show the saturation states (Ω) in typical seawater for calcite (Ω = 4.3), aragonite (Ω = 3.1) and vaterite (Ω = 1.2) are significantly elevated following the release and diffusion of the cytoplasmic bicarbonate (Ωcalcite = 95.7; Ωaragonite = 68.5; Ωvaterite = 25.9). These increases in Ω significantly reduce the activation energy for nuclei formation thresholds for all three polymorphs, but only vaterite nucleation is energetically favored. In the post-lysis seawater, vaterite’s nuclei formation activation energy is significantly reduced from 1.85×10-17 J to 3.85×10-20 J, which increases the nuclei formation rate from highly improbable (<< 1.0 nuclei cm-3 sec-1) to instantaneous (8.60×1025 nuclei cm-3 sec-1). The proposed model for homogenous nucleation of calcium carbonate in seawater describes a mechanism through which the initial step in the production of carbonate sediments may proceed. It also presents an additional role of photosynthesizing microbes and their viruses in marine carbon cycles and reveals these microorganisms are a collective repository for concentrated and reactive dissolved inorganic carbon (DIC) that is currently not accounted for in global carbon budgets and carbonate sediment diagenesis models.